Implementing Mitochondrial Cytochrome Oxidase Subunit I (COI) Gene in Identifying Rhopalosiphum Koch. spp. In Iraqi Environments (World Journal of Experimental Biosciences, 2021)
Aphid species are usually identified by microscopic examination of morphological features. This process requires significant expertise and is difficult in immature aphid stages that lack many diagnostic morphological features in addition to the characterization of polymorphism in this group. The current study used molecular technique by detection of mitochondrial cytochrome oxidase subunit I (COI) gene using Lep primer pairs (Forward and Reverse) to identify local Rhopalosiphum Koch. spp. these aphid samples were previously characterized by morphological features, and then compared between these two identification methods. Only 5% of samples were not detected by this primer. The DNA amplification product of the mitochondrial COI gene was subjected to direct sequencing. The sequences of the mitochondrial COI gene were obtained from 11 samples and each sample consisted of approximately 710 nucleotides. The results were compared to the Genbank database of the NCBI (National Center for Biotechnology Information), and The sequencing results showed that the 10 samples of Rhopalosiphum had percentage similarities between 98-100% with Rhopalosiphum Padi and Rhopalosiphum miadas, and one sample couldn’t find similarity to them in GenBank. The present study approves the importance of designing a specific primer that can differentiate between local Rhopalosiphum spp. that could improve the misidentification problems that are intrinsic to morphological features.